Digital Literacy and Teacher Efforts in its Utilization in Islamic Religious Education (PAI) Learning - Taufiqurrahman, Muhammad (Proceeding International Conference on Religion, Science and Education, 2024)
This study aims to analyze digital literacy among students and its correlation with student learning outcomes in Islamic Religious Education subjects and to find out the efforts made by teachers in utilizing digital literacy in PAI learning at SMPN 05 Lebong, Bengkulu Province. Digital literacy refers to an individual’s ability to access, evaluate, used, shared and create information effectively using digital technology. In the context of PAI learning, digital literacy is becoming increasingly important due to the influence of technology on social interaction and access to religious information. This study uses mixed methods with qualitative and quantitative approaches. Data was collected through a digital literacy questionnaire given to 109 grade VIII students and in-depth interviews with PAI teachers. The questionnaire was distributes to measure students’ digital literacy index and how much correlation it has with student Islamic education learning outcomes. Interviews with teachers were used to identify the strategies used in teaching PAI and the obstacles encountered in integrating digital literacy. The results of this study found out that there was a positive correlation between students’ digital literacy index and Islamic education learning outcomes and an r value of 0.5017. Then there are 3 important efforts made by PAI teachers:1) becoming a skilled and technology-based facilitator,2) building communication with the headmaster,3) being innovative and creative. It is hoped that digital literacy in PAI learning will provide students with a better understanding of technology, as well as being a driving force for teachers to continue to facilitate the use of digital in PAI learning. The implications of this research can be the basis for curriculum development that is more adaptive to technological developments and student learning styles. In addition, this research also contributes to the literature regarding the integration of digital literacy in PAI learning, which is still relatively under-researched.